Music, Resilience and Tradition Through Ethnographic Documentary. Analysis of Cantadoras. Memories of Life and Death in Colombia (Carrillo, 2017) - Mauri Estupiña, David (2025)
Based on a methodology combining film analysis with an interview, this article analyzes Cantadoras. Memories of Life and Death in Colombia (Carrillo, 2017). In it, five women singers from Colombia’s Caribbean and Pacific regions stand as examples of safeguarding the inherited collective memory through music and their daily work, which resists the various consequences of the country’s armed conflict. The article, in this way, approaches the ethnographic documentary, conceived and exercised from the ethical and political point of view, and understood as an audiovisual tool that allows exercise as a historical document and, at the same time, allows to make visible subaltern voices, whose story and songs are constituted as testimonies of hope, identity, liberation and social cohesion in their respective communities.